(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article deals with the problems and gives the estimation of the tendencies of the modern stage of development the agrarian sector of Ukraine’s economy. It is defined that action of new social-economic and geopolitical factors caused the appearance the whole number of problems of branch development. Among them are the reduction of quantity of small farms and private peasant farms, inadequate development of countryside infrastructure, improving social welfare, increase revenues to community budgets.